A4NH 2020 annual report highlights: Gender - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2021)
This includes three highlights document for Gender Research of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: A4NH research shines in new CGIAR GENDER platform Highlight 2: Addressing women’s empowerment throughout the value chain Highlight 3: Equity in food systems transformation